Type 2C protein phosphatase clade D family members dephosphorylate guard cell plasma membrane H+-ATPase. Issue 4 (11th December 2021) - Akiyama, Mitsumasa; Sugimoto, Hodaka; Inoue, Shin-ichiro; Takahashi, Yohei; Hayashi, Maki; Hayashi, Yuki; Mizutani, Miya; Ogawa, Takumi; Kinoshita, Daichi; Ando, Eigo; Park, Meeyeon; Gray, William M; et al.
Abstract: Plasma membrane (PM) H + -ATPase in guard cells is activated by phosphorylation of the penultimate residue, threonine (Thr), in response to blue and red light, promoting stomatal opening. Previous in vitro biochemical investigation suggested that Mg 2+ - and Mn 2+ -dependent membrane-localized type 2C protein phosphatase (PP2C)-like activity mediates the dephosphorylation of PM H + -ATPase in guard cells. PP2C clade D (PP2C.D) was later demonstrated to be involved in PM H + -ATPase dephosphorylation during auxin-induced cell expansion in Arabidopsis ( Arabidopsis thaliana ). However, it is unclear whether PP2C.D phosphatases are involved in PM H + -ATPase dephosphorylation in guard cells. Transient expression experiments using Arabidopsis mesophyll cell protoplasts revealed that all PP2C.D isoforms dephosphorylate the endogenous PM H + -ATPase. We further analyzed PP2C.D6/8/9, which display higher expression levels than other isoforms in guard cells, observing that pp2c.d6, pp2c.d8, and pp2c.d9 single mutants showed similar light-induced stomatal opening and phosphorylation status of PM H + -ATPase in guard cells as Col-0. In contrast, the pp2c.d6/9 double mutant displayed wider stomatal apertures and greater PM H + -ATPase phosphorylation in response to blue light, but delayed dephosphorylation of PM H + -ATPase in guard cells; the pp2c.d6/8/9 triple mutant showed similar phenotypes to those of the pp2c.d6/9 double mutant. Taken together, these results indicate that PP2C.D6 and PP2C.D9 redundantly mediate PM H + -ATPase dephosphorylation in guard cells. Curiously, unlike auxin-induced cell expansion in seedlings, auxin had no effect on the phosphorylation status of PM H + -ATPase in guard cells. Abstract : Type 2C protein phosphatase clade D family members redundantly dephosphorylate the penultimate C-terminal threonine residue of plasma membrane H + -ATPase in guard cells to control stomatal movement.